Two Patient Cases Illustrating the Importance of Addressing Physical and Mental Trauma as a Cause of Pain in Refugee Women - Brodda Jansen, Gunilla (Frontiers in Sociology, 2020)
Refugees and more so women than men are often seeking medical care for a wide range of health-related problems, among which persistent pain have long been recognized as a defining feature. When treating refugee women for any condition, pain and its consequences needs to be addressed in the rehabilitation efforts. It is therefore essential that health professionals engaged in the care of refugee women are familiar with the physiology of pain mechanisms including the biopsychosocial model of pain, as well as the best evidence-based practice in managing pain, acute as well as chronic. Persistent or chronic pain not only cause disability and restricted functioning but also produce psychological impairments, compounding the impact on overall personal and social functioning. Yet, the research literature on health regarding refugees is predominantly targeted at mental health problems without specific reference to pain and pain as a significant cause of distress and disability due to migration (pre-and post). Pain as a consequence of torture is also an issue that is under assessed when refugees are seeking medical aid for pain related problems. When aiming at treating refugee women with disabling pain, one can use the same intervention methods that are being used for other chronic pain states. Professionals need, however, to be able work with less written information and work in close co-operation with interpreters. Reviews of the rehabilitation literature has noted a lack of scientifically rigorous studies of multicomponent interventions for refugees. Only few studies have evaluated outcomes of pain management, and the quality of evidence they provide is very low. The small number of randomized controlled trials and the resulting paucity of information means that recommendations amount to good clinical practice for refugee women with persistent pain is lacking. The aim of this article is to point out important areas that need to be addressed within the health care system in order to improve the health care for refugee women. Pain is a common cause for refugee women to seek medical aid as is a costly burden for the society and decrease quality of life for these women